Avaliação de parâmetros da resposta imunológica na co-infecção pelo HIV-1 e vírus das hepatites C e G (HGV/GBV-C) - Baggio-Zappia, Giovana Lotici [UNIFESP] (2009)
GBV-C co-infection is frequent in humans and could last for years without clinical symptoms. GBV-C is a flavivirus composed by a single positive RNA strain, closely related to HCV. Initially in its discovery GBV-C was associated with non-A-B hepatitis. However, subsequent studies failed to associate GBV-C with any known human disease and the virus became neglected until a series of studies associated the virus with prolonged survival in HIV infected recipients. Studies evaluating the co-infection presents conflicting results whereas triple HIV-HCV-GBV-C infection remains to be clarified. With the aim to evaluate the effect of GBV-C upon HIV and HIV-HCV co-infected patients, we included a cohort of 159 HIV-seropositive patients from CCDI-UNIFESP. The patients were tested for the presence of anti-E2 antibodies and GBV-C RNA. Of the 107 HIV seropositive patients negative to HCV infection, 41 (38,3%) were positive to GBV-C infection markers, of whom 17 (15,8%) were GBV-C viremic and 24 (22,4%) were positive to anti-E2 antibodies. Of the 52 HIV-HCV co-infected patients, 24 (46,1%) were positive to GBV-C infection markers, of whom 14 (26,9%) were viremic and 10 (19,2%) presented anti-E2 antibodies. Epidemiological data were collected; virological and immunological markers and also hepatic function were evaluated. Besides, IFN- and IL-2 production on CD4, T CD8 and T cells and CD38 activation marker on T CD4 and T CD8 cells were also evaluated. No significant differences on HIV viral load nor on T CD4 and T CD8 cell counts were observed, according to the infection profile. Immune response, evaluated by the IFN- and IL-2 production and by the CD38 expression did not differ among the groups studied. Univariate analysis demonstrated higher ALT, AST and GGT levels in the HIV-HCV co-infetced and HIVHCV- GBV-C triple infected patients. The multivariate analysis demonstrated that the GBV-C influences ALT levels on triple infected patients. Our results demonstrate that GBV-C does not exerts beneficial effects upon chronically HIV infected patients, unlike, it can cause hepatic overload, as demonstrated by the higher ALT levels in the HIV-HCV-GBV-C triple infected patients. In the light of these results, is reasonable to prudently consider this interaction until the possible pathological role of GBV-C on this situation is completely excluded.